Programa para diseño de cimentaciones superficiales - Ramírez-D’Avanzo, Dilana (Instituto Tecnológico de Costa Rica, 2008)
The laying of foundation constitutes the intermediate element which transmit the load of an structure in a way that it doesn´t overload the capacity of the ground and that the deformities produced can be admissible for the structure. Therefore, to realize a correct laying of foundations it will be necessary to consider the geotechnical characteristics of the ground and in addition to determine the proportions to the own foundation, so that he is sufficiently resistant. Next we will develop a web based application using the programming language Ruby, and it´s complement Rails. Rails facilitate the configuration and programming of the application with the purpose to create an accessible with a rich interface tool for the user. This tool will help the user to design laying foundations as well as the structural design. This tool will create a final report with the results and data given by the user to the application. In the other hand a manual is given to the users so they can learn how to use the application.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2008.
Keywords: Capacidad de carga; Inclinación; Diseño estructural; Ruby on Rails; Deformaciones; Cohesión